Seiler`s hierarchy of endurance training needs - Seiler, S. (2016)
Total Frequency/Volume of Training High-Intensity Training Training Intensity Distribution General Periodization Details (Annual) Sports-Specific and Micro-Periodization Schemes Training-Stimuli Enhancement Pacing Training Training Taper